To simplify the expression \(3 \frac{1}{1} \times 5 \frac{1}{1} \div \frac{4}{4}\), we can follow these steps:
-
Convert the mixed numbers to improper fractions:
- \(3 \frac{1}{1} = 3 + 1 = 4\)
- \(5 \frac{1}{1} = 5 + 1 = 6\)
-
Now the expression becomes: \[ 4 \times 6 \div \frac{4}{4} \]
-
Since \(\frac{4}{4} = 1\), we can simplify: \[ 4 \times 6 \div 1 = 4 \times 6 \]
-
Now calculate \(4 \times 6\): \[ 4 \times 6 = 24 \]
So the simplified result of the expression \(3 \frac{1}{1} \times 5 \frac{1}{1} \div \frac{4}{4}\) is \(24\).